2019
DOI: 10.1096/fj.201901315r
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone enhances the recovery of hypoglycemia via ventromedial hypothalamic neurons

Abstract: Growth hormone (GH) is secreted during hypoglycemia, and GH‐responsive neurons are found in brain areas containing glucose‐sensing neurons that regulate the counter‐regulatory response (CRR). However, whether GH modulates the CRR to hypoglycemia via specific neuronal populations is currently unknown. Mice carrying ablation of GH receptor (GHR) either in leptin receptor (LepR)‐ or steroidogenic factor‐1 (SF1)‐expressing cells were studied. We also investigated the importance of signal transducer and activator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 80 publications
(182 reference statements)
2
45
0
Order By: Relevance
“…In this sense, infusion of 2-deoxy-D-glucose produced abnormal hyperactivity in the parasympathetic preganglionic neurons in mice with GHR-ablated VMH neurons. In addition, pharmacological blockers of the parasympathetic nervous system prevent the counterregulatory defects caused by GHR ablation in the VMH (56). Unlike the effects induced by GHR depletion in the POMC neurons (54), GHR-ablated VMH neurons did not affect glucoprivically induced hyperphagia (56), demonstrating that GH action in each neuronal population induces very specific effects (Figure 3).…”
Section: Gh Action In the Cns Regulates Metabolismmentioning
confidence: 95%
See 1 more Smart Citation
“…In this sense, infusion of 2-deoxy-D-glucose produced abnormal hyperactivity in the parasympathetic preganglionic neurons in mice with GHR-ablated VMH neurons. In addition, pharmacological blockers of the parasympathetic nervous system prevent the counterregulatory defects caused by GHR ablation in the VMH (56). Unlike the effects induced by GHR depletion in the POMC neurons (54), GHR-ablated VMH neurons did not affect glucoprivically induced hyperphagia (56), demonstrating that GH action in each neuronal population induces very specific effects (Figure 3).…”
Section: Gh Action In the Cns Regulates Metabolismmentioning
confidence: 95%
“…In a recent study (56), we showed that a large number of GH-responsive neurons are found in the ventromedial nucleus of the hypothalamus (VMH), a key relay station that regulates the counter-regulatory response to hypoglycemia (57). Although ablation of GHR in VMH neurons did not affect glucose tolerance or insulin sensitivity, the absence of GH action in the VMH neurons impaired the capacity of the mice to recover from insulininduced hypoglycemia and significantly decreased the counter-regulatory response induced by 2-deoxy-Dglucose injection (56). The effects of GH regulation on the counter-regulatory response are likely mediated by the parasympathetic nervous system.…”
Section: Gh Action In the Cns Regulates Metabolismmentioning
confidence: 99%
“…Since GH also regulates insulin sensitivity, part of this effect may be mediated by the brain as well. Previous studies investigated the physiological role of GH signaling in leptin receptor (LepR)-expressing cells [ 79 , 80 ]. Notably, GHR ablation in LepR-expressing cells led to impaired hepatic insulin sensitivity [ 79 , 80 ].…”
Section: Central Regulation Of Metabolism By Ghmentioning
confidence: 99%
“…Evidence for the importance of GH-responsive neurons in the hypothalamus in modulating metabolism was reported in several studies (35)(36)(37)(38). We have recently identified a unique population of nutrient-sensing leptin receptor (LepRb)-GHR expressing neurons that regulate hepatic glucose production and lipid metabolism, suggesting that these neurons are crucial for the metabolic functions of GHR-neurocircuitry (18).…”
Section: Discussionmentioning
confidence: 93%